2013
DOI: 10.1103/physrevc.88.011601
|View full text |Cite
|
Sign up to set email alerts
|

Faddeev-type calculation of three-body nuclear reactions including core excitation

Abstract: Background: The core excitation, being an important reaction mechanism, so far is not properly included in most calculations of three-body nuclear reactions.Purpose: We aim to include the excitation of the core nucleus using an exact Faddeev-type framework for nuclear reactions in the three-body (core + neutron + proton) system. Methods:We employ Alt, Grassberger, and Sandhas (AGS) integral equations for the three-particle transition operators and solve them in the momentum-space framework. The Coulomb interac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
200
3
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(212 citation statements)
references
References 43 publications
(97 reference statements)
8
200
3
1
Order By: Relevance
“…A subsequent theoretical work [19] suggested that a reduction in cross section due to core excitation, not taken into account in either DWBA or ADWA analyses, would result in lower values of S being extracted from experimental data at higher beam energies. The current data are not discriminating enough to confirm, or refute, the effects of core excitation in the reaction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A subsequent theoretical work [19] suggested that a reduction in cross section due to core excitation, not taken into account in either DWBA or ADWA analyses, would result in lower values of S being extracted from experimental data at higher beam energies. The current data are not discriminating enough to confirm, or refute, the effects of core excitation in the reaction.…”
Section: Discussionmentioning
confidence: 99%
“…However, they could equally show a downward trend with increasing beam (or equivalent deuteron) energy. Faddeev-type calculations of 10 Be + d that included dynamic core excitation were subsequently performed by Deltuva [19] for the four energies used in the experiment . The core excitation effects he found in that work are shown in the right panel of Figure 2 (the line shown here is the red line in Figure 5 of [19]).…”
Section: Spectroscopic Factors Formentioning
confidence: 99%
See 1 more Smart Citation
“…Excitations of the target nucleus have been directly or indirectly accounted for in the CDCC [8] approach, adiabatic threebody models [9] and, recently, in the distorted-wave Born approximation model [10]. Important core excitations effects have also been found in Faddeev-type calculations for nuclear reactions [11]. Multiple core excitations are in particular needed when deuteron stripping reactions populating resonance states of the final nucleus are considered, as it is the case for the CDCC extension to transfer reactions in the continuum [12].…”
Section: Introductionmentioning
confidence: 99%
“…These models are accurate in nuclei with a strong clusterization into few stable fragments as it occurs in the light region of the Segrè Chart. When moving to the study of heavier isotopes, these models require some extension or additional ingredients [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%